A BRIEF INTRODUCTION TO NEUTRON ACTIVATION ANALYSIS IN CHINA - Weizhi, Tian (The Nucleus, 2020)
The history, the major achievements in both methodology and applications, the current trends and future perspectives of neutron activation analysis (NAA) in China are briefly described.